Fracture toughness measurements to understand local ductility of advanced high strength steels. (November 2019) - Frómeta, D.; Lara, A.; Casas, B.; Casellas, D.
Abstract: The determination of the material parameters that best predict the local ductility of high strength sheet materials has become the focus of active research. Even though several correlations have been proposed, they can sometimes be not accurate enough and discussion is still open on this topic. This paper investigates the suitability of different fracture toughness measurements for local ductility prediction in multiple advanced high strength steels (AHSS). Fracture toughness is characterized by means of essential work of fracture and Khan tear tests. The results show that the essential work of fracture, we, correlates well with different local formability (HER, critical bending angle from V-bending tests and local strain at fracture from uniaxial tensile tests) and crash resistance parameters (energy absorbed in axial impact tests). It confirms that fracture toughness, measured in the frame of fracture mechanics, is a relevant material property to rationalize cracking issues associated to the local ductility of AHSS. On the other hand, it is also shown that Khan tear tests, which are conventionally used to evaluate the fracture resistance of thin metal sheets, can overestimate crack propagation resistance and offer a poor prediction ability for local formability and crash performance.